Penyebaran dan Dampak Cyberporn pada Aplikasi X: Tinjauan Hukum dan Pengaruh Sosial dalam Lingkungan Media Sosial - Maharani, Farah Dilla Puspita (UM Purwokerto Press, 2024)
Cyberpornography, or cyberporn, is a form of digital crime that is increasingly widespread along with the rapid development of information and communication technology. This phenomenon not only damages people's morals, but also has significant negative impacts, such as vulnerability to sexual violence, psychological disorders and social instability. This article explores various aspects of cyberporn, including its definition, impact, and mitigation efforts. The research methods used include literature analysis and relevant case studies. The findings show that cyberporn impacts three main groups: individuals who are objects or models in pornographic content, the general public, and individuals who are driven to commit new crimes after consuming the content. Comprehensive preventive measures from authorities, social media platforms and society are needed to tackle this problem. Steps such as strengthening regulations, increasing supervision, public education, and international cooperation are considered essential to reduce the spread and negative impacts of cyberporn. It is hoped that this article can provide insight and contribute to the development of policies and law enforcement strategies that are more effective in dealing with cyberpornography.